Stability of ascorbic acid in serum and plasma prior to analysis - Ching, Simon YL; Prins, Alex W; Beilby, John P (Annals of clinical biochemistry, 2002)
Introduction: The stability of ascorbic acid in serum and plasma prior to analysis was studied. Methods: Blood samples were collected from ten healthy subjects into Vacutainer tubes containing either dipotassium EDTA, lithium-heparin or no additive. Ascorbic acid was analysed following immediate separation and preservation of samples, following delayed separation for 2 h and after delayed deproteinization and preservation for 2, 5 and 8 h. Deproteinization and preservation were achieved using a solution containing perchloric acid, EDTA and dithiothreitol. Ascorbic acid was analysed by high-performance liquid chromatography. Results: Blood collected into EDTA and separated, deproteinized and preserved immediately gave the highest yield of ascorbic acid. Loss of analyte after delayed separation was least for EDTA tubes (median 7%, range 4-13%), followed by lithium-heparin (median 18%, range 10-32%) and serum (median 26%, range 14-50%). Immediate separation of samples but delayed deproteinization and preservation also resulted in substantial losses of ascorbic acid. Conclusion: Minimum loss of ascorbic acid is achieved if blood is collected into tubes containing dipotassium EDTA and separated within 2 h, followed by immediate deproteinization and preservation.